Carbon Transfer Efficiency and Risk of Fisheries Collapse in Three Large Marine Ecosystems Around China - Chen, Dongxing; Wang, Xutao; Hou, Minchi; Wang, Qiabin; Liu, Qianqian; Huang, He; Zhang, Yafeng (Frontiers in Marine Science, 2022)
Fisheries catch is determined by a complex combination of biological and industrial factors. In this study, using data from the online database Sea Around Us from 1950 to 2018, we assessed the risk of fisheries collapse for the three Large Marine Ecosystems (LMEs) around China by analyzing the carbon transfer efficiency, mean trophic level and mean maximum length of fisheries catch and expansion factor, and compared them with other LMEs, especially the Humboldt Current and the North Sea LMEs, which ever went through fishery collapse. Our calculation found high carbon transfer efficiencies in LMEs around China, suggesting large fishing efforts compared with LMEs with similar primary production. While marine fish landings didn’t decline significantly, they are maintained by potential resources based on offshore and deep expansion and fishing on lower-trophic-level species and juvenile fish. However, the potential resources have been largely consumed in the East China Sea and South China Sea LMEs where the ratios of primary production required to sustain catches to the total primary production (%PPR) larger than 50%. In contrast, this ratio in the Yellow Sea LME was lower, but was still higher than the sustainable ratio in the Humboldt Current LME. Without proper fisheries management, the three fisheries around China are likely to collapse as the North Sea LME did in the 1970s.